Bunraku and Kwagh-hir: A Comparative Exploration of Cultural Dialogues and Identity in the Puppet Theatres of Nigeria and Japan - Aguoru, Adedoyin (Mindscape: A Journal of English & Cultural Studies, 2025)
Ethnographical studies, cultural studies and historical narratives synonymously acknowledge preservation of national theatres as being fundamental to national identity and that national theatres serve as cultural databanks for nations. Dominant studies on Nigerian and Japanese theatre traditions have mainly focused on the examination of theatrical forms as national theatres and have examined thematic, dramaturgical and technical thrusts. They have not been concerned with possible comparative transnational and transcontinental study of these traditions as national treasures that reinforce the identity of peoples. This comparative explication of two selected Nigerian and Japanese puppetry traditions, the Japanese (Bunraku) and Nigerian Tiv (Kwagh-hir), is carried out with a view to advancing the significance of these art forms. Chikamatsu Monzaemon’s works including The Love Suicides at Sonezaki represent the Japanese (Bunraku) and the Anor Gyura Kwagh-hir performance the Nigerian Tiv (Kwagh-hir) puppetry traditions.